2009
DOI: 10.1111/j.1751-7915.2008.00073.x
|View full text |Cite
|
Sign up to set email alerts
|

Atrazine biodegradation in the lab and in the field: enzymatic activities and gene regulation

Abstract: SummaryAtrazine is an herbicide of the s‐triazine family that is used primarily as a nitrogen source by degrading microorganisms. While many catabolic pathways for xenobiotics are subjected to catabolic repression by preferential carbon sources, atrazine utilization is repressed in the presence of preferential nitrogen sources. This phenomenon appears to restrict atrazine elimination in nitrogen‐fertilized soils by indigenous organisms or in bioaugmentation approaches. The mechanisms of nitrogen control have b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
36
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 74 publications
(38 citation statements)
references
References 76 publications
(191 reference statements)
2
36
0
Order By: Relevance
“…Complete mineralization is the most favorable way of biodegradation; however, the vast majority of the xenobiotics biodegradation pathways (including triazines) end in the formation of by-products. Formation of ametryn metabolites during the experiments presented in this work is partially in agreement with the reactions of atrazine biodegradation, where the formation 2-hydroxyatrazine has been observed in many species (Atrazine Pathway Map, 2017; KEGG Atrazine degradation -Reference pathway, 2017; Govantes et al, 2009;Solomon et al, 2013;Abigail et al, 2013), while deethylation of ethanamine substituents seems to be characteristic for fungal strains and mammals (Chirnside et al, 2011;Pereira et al, 2013, Sciali et al, 2014. Figure 6.…”
Section: Discussionsupporting
confidence: 86%
“…Complete mineralization is the most favorable way of biodegradation; however, the vast majority of the xenobiotics biodegradation pathways (including triazines) end in the formation of by-products. Formation of ametryn metabolites during the experiments presented in this work is partially in agreement with the reactions of atrazine biodegradation, where the formation 2-hydroxyatrazine has been observed in many species (Atrazine Pathway Map, 2017; KEGG Atrazine degradation -Reference pathway, 2017; Govantes et al, 2009;Solomon et al, 2013;Abigail et al, 2013), while deethylation of ethanamine substituents seems to be characteristic for fungal strains and mammals (Chirnside et al, 2011;Pereira et al, 2013, Sciali et al, 2014. Figure 6.…”
Section: Discussionsupporting
confidence: 86%
“…Although s-triazine transport by degrading strains has not been studied in detail, indirect evidence of an s-triazine transporter has been documented for several organisms (18,48,54), including Pseudomonas sp. strain ADP (15,22,38). Proximity to the cyanuric acid utilization atzDEF operation and coregulation by the general nitrogen control system and AtzR suggest that they may be involved in the transport of cyanuric acid.…”
Section: Lttrs Andmentioning
confidence: 99%
“…In bioremediation of groundwater study, atrazine is readily biodegraded under controlled conditions (Shapir et al, 2007). It was found that biodegrading capacity is inhibited in the presence of external nitrogen and carbon sources (Govantes et al, 2009). On the other study of Agrobacterium radiobactor strain J14a, the degradation rate of atrazine was enhanced in Sequential Batch Biofilm Reactor (SBBR) after the additional supply of carbon source (Protzman et al, 1999).…”
Section: Biological Methodsmentioning
confidence: 99%